Functional electrical stimulation: an overview. - Hambrecht FT (Pacing & Clinical Electrophysiology, 1989)
The development of future neural prostheses involves much more than connecting commercially available stimulators to disabled individuals. Safe and effective operation of prostheses requires fundamental studies of the electrode-tissue interface. The electrochemistry of the interface must be controlled to prevent toxic byproducts. Histopathological studies of stimulated tissue are necessary to establish safe limits of stimulation and to determine mechanisms of neural damage when it does occur. Electrophysiological studies elucidate which neural pathways are excited and help in the design of more selective electrode arrays. Biomaterials are required that protect the implant from the hostile environment of the body. Presently available materials are being improved and totally new materials are being developed. One of the goals of neural prostheses developers is a nonhermetic packaging material that can be applied to miniature implants without appreciably increasing their size. The techniques used to make integrated circuits on silicone substrates are ideally suited to making ultraminiature electrodes with self-contained electronic signal processing. Both integrated circuit stimulating and recording electrodes are being designed and fabricated.